DO MODERNISMO AO ALGORITMO: EVOLUÇÃO E PERSPECTIVAS DA POLÍTICA PATRIMONIAL BRASILEIRA - Erthal, Thiago Serpa (2020)
Culture is a broad term that, unless restricted in its spatial and temporal dimension, has a polysemy that hinders its conceptualization. That is why, to understand the public policy of cultural heritage protection in the first two decades of the 21st century and its perspectives, it is pertinent to make an investigation of the actors and theoretical premises involved in the selection of material and immaterial goods to be safeguarded. This is the purpose of this article. To achieve this, the influence of modernist thought was initially analyzed in the first three decades since its inception (1937-1967). In this so-called heroic phase, the intellectual elite's conception of what should symbolically represent national culture prevailed. Then, the approximation of cultural heritage with economic development significantly changed the valuation and management parameters. Several funding plans have directly intertwined with the theoretical selection criteria, influencing them and being influenced by a complex dynamic of thought and action. In this context, it was concluded that one of the hallmarks of patrimonial public policy in the two decades of the 21st century was the relative political-administrative decentralization of its execution, albeit with setbacks. Finally, a potential migration from this centralized or decentralized state role to large technology companies was proposed in perspective, especially with the diffusion of the culture of algorithms.